Pemulihan Ekonomi Kota Pontianak melalui Digitalisasi UMKM Berbasis Ekonomi Kreatif - Suhedi, Suhedi; Alfarisi, Muhammad Adib (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Economic issues within society become subjects of rigorous debate, especially in times of crisis such as the COVID-19 pandemic. Various recovery initiatives are undertaken by both governmental entities and the private sector, aimed at expediting the process of digital transformation within the micro, small, and medium enterprises (MSMEs) sector. This research is specifically focused on Pontianak City, situated in West Kalimantan, with the primary objective of fostering economic growth by harnessing the potential of MSMEs as a vehicle for swift recovery and the facilitation of a digitalized creative economy. This study employs William F. Gluk's theory on the economic marketing strategies employed by companies operating within the specific environmental challenges they face to attain their objectives. The authors employ qualitative research methods to comprehensively analyze and interpret the social and community issues associated with this endeavor. The findings of this research indicate that MSMEs in Pontianak City possess considerable potential for augmenting productivity and enhancing competitiveness. Consequently, the local products and services generated exhibit a distinctive competitive advantage, rendering them capable of penetrating the national-scale market. Furthermore, the authors contend that Pontianak City, being the provincial capital and a prominent business hub within West Kalimantan, enjoys the support of numerous factors, including its sizable population and the accelerating digitalization trend. This, in turn, catalyzes the growth of the local wisdom economy within a digital marketplace framework. Consequently, the economy of Pontianak City is poised for long-term development, driven by the rapid and sustained transformation ushered in by digitalization.